DESIGN AND IMPLEMENTATION OF SMART HOME CONTROL SYSTEM BASED ON INTERNET OF THINGS - LIU, WEN YEE (Universiti Malaysia Sarawak, (UNIMAS), 2019)
This project describes on the design and implementation of smart home control system which can helps to save energy and reduce power wastage. This control system is based on four different sensors which including the motion sensor, smoke sensor, ultrasonic sensor, and temperature and humidity sensor. Arduino MEGA2560 board acts as the main control unit and ESP8266 Wi-Fi module as a communication protocol. The users can control the home systems easily by using the sensors, such as controlling the lights, door and window. These systems are easily controlled and can be monitored via user-friendly interface for smartphones. IoT based home automation system is applicable in this project, whereby the home automation systems can be monitored through mobile phones with Internet connections. Besides, an addition feature that enhances the protection of house is added to the system. Mobile applications such as ThingView and Virtuino are installed in the mobile phones to allow the users to monitor the home appliances as well as the security and safety of the house. An alerting message is sent to the smartphone when fire accident or burglar incident happens. This message alerts the users and thus prevent the house from danger. The main advantage of this smart home control system is that it is a sensible, secure and easily configurable system that provides the users with a smart and neat home automation. Thus, all the objectives are achieved